Screw loosening in the Dynesys stabilization system: radiographic evidence and effect on outcomes - Ko, Chin-Chu; Tsai, Hsiao-Wen; Huang, Wen-Cheng; Wu, Jau-Ching; Chen, Yu-Chun; Shih, Yang-Hsin; Chen, Hung-Chieh; Wu, Ching-Lan; Cheng, Henrich (Neurosurgical focus, 2010)
Dynamic stabilization systems are used to stabilize degenerative lumbar spondylosis. Loosening of the pedicle screws in such nonfusion implants is predictable. This retrospective study evaluated the incidence of screw loosening and its effect on clinical outcomes.